Personnel Policy of Mid-1970s and Ruling Nomenclature in Representations of Soviet Public - A. S. Stoletova (Научный диалог, 2020)
Using the example of epistolary sources extracted from the fund No. 5 “Apparatus of the Central Committee of the CPSU (1949-1991)” of the Russian State Archive of Contemporary History, the problem of the history of the personnel policy development in the USSR, that is insufficiently covered in historical science, is examined in the article. The circumstances that had developed by the mid-1970s in the light of the decree of the Central Committee of the CPSU of February 12, 1975 “On the state of criticism and self-criticism in the Tambov Regional Party Organization” are described. The question is raised about the transformation of the Party-Soviet nomenclature, its social orientations and moral guidelines. The results of a comparative analysis of letters from various regions of the USSR are presented. On their basis the conclusions about the socialist ideals of Soviet citizens and the psychology of individualism contrary to them, the mentality of accumulation, which are affirmed among the political elite, are drawn. The circumstances of the embourgeoisement of regional leaders, personal corruption, especially abuse in the exercise of property rights, are commented. It is stated that gradually illegal actions, in the absence of strict measures to dismiss executives from their posts, became systemic, taking the form of custom. The author comes to the conclusion that the political space, socio-economic structure and the spiritual and moral sphere of society have evolved towards consumer, private ownership, property interests and needs.